Phase 1/2 Study of Lumasiran for Treatment of Primary Hyperoxaluria Type 1: A Placebo-Controlled Randomized Clinical Trial. Issue 7 (July 2021) - Frishberg, Yaacov; Deschênes, Georges; Groothoff, Jaap W.; Hulton, Sally-Anne; Magen, Daniella; Harambat, Jérôme; van't Hoff, William G.; Lorch, Ulrike; Milliner, Dawn S.; Lieske, John C.; Haslett, Patrick; Garg, Pushkal P.; et al.
Visual Abstract: Abstract : Background and objectives: In the rare disease primary hyperoxaluria type 1, overproduction of oxalate by the liver causes kidney stones, nephrocalcinosis, kidney failure, and systemic oxalosis. Lumasiran, an RNA interference therapeutic, suppresses glycolate oxidase, reducing hepatic oxalate production. The objective of this first-in-human, randomized, placebo-controlled trial was to evaluate the safety, pharmacokinetic, and pharmacodynamic profiles of lumasiran in healthy participants and patients with primary hyperoxaluria type 1. Design, setting, participants, & measurements: This phase 1/2 study was conducted in two parts. In part A, healthy adults randomized 3:1 received a single subcutaneous dose of lumasiran or placebo in ascending dose groups (0.3–6 mg/kg). In part B, patients with primary hyperoxaluria type 1 randomized 3:1 received up to three doses of lumasiran or placebo in cohorts of 1 or 3 mg/kg monthly or 3 mg/kg quarterly. Patients initially assigned to placebo crossed over to lumasiran on day 85. The primary outcome was incidence of adverse events. Secondary outcomes included pharmacokinetic and pharmacodynamic parameters, including measures of oxalate in patients with primary hyperoxaluria type 1. Data were analyzed using descriptive statistics. Results: Thirty-two healthy participants and 20 adult and pediatric patients with primary hyperoxaluria type 1 were enrolled. Lumasiran had an acceptable safety profile, with no serious adverse events or study discontinuations attributed to treatment. In part A, increases in mean plasma glycolate concentration, a measure of target engagement, were observed in healthy participants. In part B, patients with primary hyperoxaluria type 1 had a mean maximal reduction from baseline of 75% across dosing cohorts in 24-hour urinary oxalate excretion. All patients achieved urinary oxalate levels ≤1.5 times the upper limit of normal. Conclusions: Lumasiran had an acceptable safety profile and reduced urinary oxalate excretion in all patients with primary hyperoxaluria type 1 to near-normal levels. Clinical Trial registry name and registration number: Study of Lumasiran in Healthy Adults and Patients with Primary Hyperoxaluria Type 1, NCT02706886